1998
DOI: 10.1093/clinchem/44.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin I measurement with the ACCESS® immunoassay system: analytical and clinical performance characteristics

Abstract: We evaluated the ACCESS® cardiac troponin I (cTnI) immunoassay as a marker for myocardial infarction (MI). Total imprecision was 6.0% to 13.5%, the minimum detectable concentration was 0.007 μg/L, and the limit of quantitation was 0.046 μg/L. Comparison of cTnI measurement between the ACCESS and Stratus systems (n = 114) showed a proportional difference: ACCESS cTnI = 0.0996 Stratus cTnI + 0.049 μg/L (r = 0.811). Fifty-nine of 61 ambulatory patients without cardiac symptoms had no detectable cTnI (95% range, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…Cardiac troponin is tightly bound to the sarcomeric actin filament, and without cardiac damage, circulating cTnI concentrations in healthy subjects are low. 25,26 Our finding that healthy dogs have cTnI near or below the lower detection limit of the assay agrees with previous reports in human 57,58 and veterinary medicine. 13,14,19,20 Specifically, our median cTnI of 0.03 ng/mL in 176 healthy dogs is comparable to that of a previous study that reported a median cTnI of 0.02 ng/mL in 41 clinically healthy dogs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cardiac troponin is tightly bound to the sarcomeric actin filament, and without cardiac damage, circulating cTnI concentrations in healthy subjects are low. 25,26 Our finding that healthy dogs have cTnI near or below the lower detection limit of the assay agrees with previous reports in human 57,58 and veterinary medicine. 13,14,19,20 Specifically, our median cTnI of 0.03 ng/mL in 176 healthy dogs is comparable to that of a previous study that reported a median cTnI of 0.02 ng/mL in 41 clinically healthy dogs.…”
Section: Discussionsupporting
confidence: 92%
“…The concentration of circulating cTnI is a balance between its release from the myocardium; leakage into the general circulation; degradation by serum proteases; and clearance by the kidney, liver, and reticuloendothelial system. In humans with chronic renal failure (serum creatinine Ͼ8.0 mg/dL), troponin concentrations can be high due to decreased renal clearance, 57 but this effect apparently is more significant for cTnT measurement than for cTnI. 62 We did not specifically perform renal function tests in our study population, but given the high prevalence of chronic renal disease in older dogs, it is possible that impaired clearance of cTnI influenced our findings.…”
Section: Discussionmentioning
confidence: 95%
“…The reference ranges and cut‐offs that we adopted were based upon the experiences of our biochemistry department and on a published evaluation by Christenson et al . [13] and were as follows: (i) lower limit of detection = 0.03 ng.ml −1 , (ii) cut‐off for myocardial infarction = > 0.15 ng.ml −1 , (iii) grey area indicating possible ischaemia = 0.07–0.15 ng.ml −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The ACCESS ® Troponin I Immunoassay is a double‐monoclonal immunoenzymometric assay for quantitative determination of cardiac troponin I using magnetic separation and chemoluminescence detection and is based on the technique described by Larue et al ( 8). The results with this analytical system are available within 15 min and, according to the manufacturer’s specifications, the analytical range is 0.03–50.0 ng · ml −1 and the cut‐off value is 0.1 ng · ml −1 to be considered as the biochemical evidence of myocardial injury ( 9). If the patient expressed some precordial pain or ECG disturbance in comparison with basal ECG associated with specific cardiac enzyme impairment, a cardiologist and transthoracic echocardiography were required.…”
Section: Methodsmentioning
confidence: 99%